The cinemas in the situation of pandemia - A. O. Remizovskyi (Ukrainian Cultural Studies, 2021)
The analytical note analyzes the crisis in the movie theater industry that arose due to the Covid-19 pandemic. Static data is provided, demonstrating how the position of cinemas in the creative economy has changed negatively. Specific causes of the problem are described, models and individual measures for its solution are given. The analytical note provides recommendations to state authorities and industry representatives to compensate for the negative consequences of the pandemic.